THE IMPACT OF TECHNOLOGY ON EDUCATION - Toshpo’latov Dilshotjon; Shavkatova Gulzoda (TADQIQOTLAR, 2025)
Annotation: This article explores the role of science in modern society, emphasizing its impact on technological development, healthcare, environmental protection, and daily life. It discusses how scientific research contributes to solving global challenges such as climate change, disease prevention, and sustainable energy. The article highlights the importance of investing in science education and research institutions to promote innovation and economic growth. By analyzing recent scientific advancements, the author argues that continued support for science is essential for shaping a better and more sustainable future.